Analisis Dan Perancangan Filter Harmonik Pada Sistem Tenaga Listrik Di Pusat Penampungan Produksi Menggung Pertamina Asset Iv Field Cepu - Saleh, Syahmi, Agus Supardi, S.T., M.T (2016)
In the present study the researchers conducted a case study related to the electrical system at the Shelter Center Asset Production IV Pertamina Field Cepu. Because the industry there are several sources of harmonic components, namely Variable Frequency Drive (VFD). The research was done by using a network simulation software ETAP Power Station 12.6 with 3 pieces of system modeling nonlinear load VFD. System modeling is done with software ETAP 12.6 the results obtained for the value of Total Harmonic Distortion (THD) at THD 3rd VFD namely VFD 3 installed on Bus 10 to produce THDv in the amount of 5.01% and THDi in the amount of 17.31%, VFD 4 installed on Bus 16 produce THDv in the amount of 6.43 and THDi% in the amount of 14.93%, while for 5 VFD installed on bus 31yield THDv in the amount of 5.45% and THDi in the amount of 21.05%. The system modeling results indicate that there is still a high harmonic values then need to restore the quality of electricity to reduce their harmonic value. The improvements to the single tuned filter installation. After installation of the filter is obtained an impairment THD on the VFD 3 installed on Bus 10 to produce THDv in the amount of 0.60% and THDi in the amount of 12.23%, VFD 4 installed on Bus 16 to produce THDv in the amount of 3.50% and THDi in the amount of 4.89%, while for VFD 5 mounted on Bus 31 THDv in the amount of of 2.60% and THDi in the amount of 7.14%. Keywords: harmonic analysis, single tuned filter, electrical systems PPP Menggung Asset IV Pertamina Cepu Field